A high level of volleyball practice enhances bone formation markers and hormones in prepubescent boys - Chaari, H.; Zouch, M.; Denguezli, M.; Bouajina, I.; Zaouali, M.; Tabka, Z. (Biology of Sport, 2012)
Objectives: To examine the effects of volleyball on hormones and biochemical markers before puberty. Methods: 130 prepubescent white boys were investigated in this study. 80 prepubescent volleyball players were divided into two groups according to the duration of training: 40 (age: 11.5 ± 0.6 years), representing the high-level training group (HLG), completed 6 to 8 hours of training/week; 40 (age: 11.2 ± 0.7 years), representing the low-level training group (LLG), completed 3 to 5 hours of training/week. The other 50 non-athletic boys (age: 11.3 ± 0.2 years) were used as control subjects (C). Results: Serum concentration of growth hormone (GH), insulin-like growth factor 1 (IGF-1) and carrier protein 3 (IGFBP-3), cortisol, bone formation markers (osteocalcin [OC] and bone alkaline phosphatase [BAP], and a bone resorption marker (cross-linked C-terminal telopeptide of type I collagen [CTX] were measured. No difference in CTX was observed among the three groups. However, the HLG presented higher levels of bone formation markers (OC, BAP) compared to controls. Hormonal concentrations of GH, IGF-1, IGFBP-3, and cortisol were higher in HLG than in controls. Conclusion: Volleyball did not lead to enhanced bone turnover markers and anabolic hormones of bone after a low-training level when compared to controls. Indeed, a high-training level induces enhanced bone formation markers and basal concentration of anabolic (GH, IGF-1, and IGFBP-3) and catabolic (cortisol) hormones of bone metabolism. Therefore, basal hormone concentrations and bone formation markers were directly related to the intensity and the duration of the training level.